1974
DOI: 10.1073/pnas.71.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Actin in the Green Alga, Nitella

Abstract: Bundles of microfilaments very similar in appearance to actin are present in cytoplasmic suspensions obtained from Nitella flexilis. The microfilaments bind rabbit heavy meromyosin in arrowhead arrays similar to those produced on muscle actin. The arrowheads are removed with ATP. The results provide evidence that actin is present in green plants, probably in the form of microfilaments thought to be involved in cytoplasmic streaming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
45
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(51 citation statements)
references
References 17 publications
(19 reference statements)
5
45
0
1
Order By: Relevance
“…5), whereas control cells perfused with NBD-CI and NBD-ethanolamine show no fluorescent cables. Structural features of the actin cable network marked by NBD-Ph in these living cells confirm features previously observed in fixed cells marked with myosin fragments (16)(17)(18).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…5), whereas control cells perfused with NBD-CI and NBD-ethanolamine show no fluorescent cables. Structural features of the actin cable network marked by NBD-Ph in these living cells confirm features previously observed in fixed cells marked with myosin fragments (16)(17)(18).…”
supporting
confidence: 85%
“…The giant cells of characean algae show rapid rotational cytoplasmic streaming. Electron and fluorescence microscopic studies employing myosin fragments have identified subcortical actin cables that are believed to participate in the generation of the streaming in these cells (16)(17)(18). These cables form unambiguous structures attached to the chloroplast files.…”
mentioning
confidence: 99%
“…We expected that if the cytoplasm behaves as an incompressible fluid confined in a container, the anterior-directed cortical shear force would generate countercurrent (posterior-directed) flow in the central region of the cell. In characean algae, while streaming occurs throughout the cell, the driving force for streaming is generated by myosin XI in a layer just beneath the cell surface (4,(16)(17)(18)(19)(20)(21)(22)(23). For characean algae, a hydrodynamic simulation assuming surface myosin as the sole active force generator demonstrated that the force transmitted toward the central cytoplasmic region due to the viscosity of the cytoplasm quantitatively accounts for cytoplasmic streaming (4).…”
mentioning
confidence: 99%
“…It goes up along one hemicylinder to the node and comes down along the other. More than 30 years ago, it has been discovered that such a course was related to the orientation of actin bundles and their AF subunits [Kersey, 1974;Palevitz et al, 1974;Palevitz and Hepler, 1975;Kersey et al, 1976]. Indeed, actin bundles align with the cytosplasmic flow and contain AFs arranged with the same polarity, i.e.…”
Section: Actin Bundles In Cytoplasmic Streaming and Transvacuolar Strmentioning
confidence: 99%